A distributed dynamic event-triggered mechanism to HMM-based observer design for H∞ sliding mode control of Markov jump systems. (August 2022) - Jiang, Baoping; Wu, Zhengtian; Karimi, Hamid Reza
Abstract: This paper is devoted to investigating asynchronous state observer design for H ∞ analysis of Markov jump systems with partial mode information through sliding mode control approach. In order to enhance the reliability and efficiency of communication network, a novel distributed dynamic event-triggered scheme is proposed. Firstly, due to partial information on the operation of system jumping modes, a continuous-time hidden Markov model (HMM) based asynchronous state observer relying on the triggered output measurement is designed, based on which an integral sliding surface function is proposed; Secondly, by proposing an asynchronous sliding mode control law, the finite-time reachability of estimated trajectories onto the predefined sliding surface is ensured; Thirdly, the stochastic stability with a prescribed H ∞ disturbance attenuation level is analyzed for the considered closed-loop systems through linear matrix inequality; Finally, a numerical example is presented to verify the validity of the proposed control scheme.